CO2 Capture using a Superhydrophobic Ceramic Membrane Contactor. (August 2015) - An, Lin; Yu, Xinhai; Yang, Jie; Tu, Shan-Tung; Yan, Jinyue
Abstract: Wetting and fouling of membrane contactor result in performance deterioration of membrane gas absorption system for CO2 post-combustion capture of coal-fired power plants. To solve these problems, in this study, a superhydrophobic ceramic (SC) membrane contactor was fabricated by chemically modification using 1H, 1H, 2H, 2H-perfluorooctylethoxysilane (FAS) solution. The membrane contactor fabrication costs for both SC membrane and PP (polypropylene) membrane contactors per unit mass absorbed CO2 were roughly the same. However, by using the SC membrane, the detrimental effects of wetting can be alleviated by periodic drying to ensure a high CO2 removal efficiency (˃90%), whereas the drying does not work for the PP membrane. The SC membrane contactor exhibited a better anti-fouling ability than the PP membrane contactor because the superhydrophobic surface featured a self-cleaning function. To ensure continuous CO2 removal with high efficiency, a method that two SC membrane contactors alternatively operate combined with periodic drying was proposed.